The effect of dynamic stretching on performance measurement among badminton player in Faculty of Education, Universiti Teknologi Mara / Mohd Hafis A Samad - A Samad, Mohd Hafis (Faculty of Education, 2014)
This study focuses on the type of dynamic and static stretching that demonstrate the effectiveness toward body power, flexibility and speed. The purpose of this study was to identify the effectiveness of dynamic stretching toward badminton player especially. Research aims to investigate the performance of the badminton players after and before implementing dynamic and static stretching so as to know the effects of dynamic and static stretching. This study was conducted in two different days of the implementation the both types of dynamic and static stretching for pre and post-test. Results showed that dynamic stretching provide more advantages toward each type of training as determined during the test. This study hopes to provide information and assist the players, coaches, teachers and anyone concerned to choose the stretching techniques either dynamic or static stretching that can contribute to improvement in sport performance.